Model komunikacijskoga kanala digitalnoga sustava satelitske radiodifuzije sa zemaljskom retransmisijom : doktorski rad - Bačić, Iva 1984; Malarić, Krešimir (Zagreb : I. Bačić ; Fakultet elektrotehnike i računarstva, 2014)
SAŽETAK: U ovom radu analizira se sustav satelitske radiodifuzije do malih uređaja sa zemaljskom retransmisijom, DVB-SH-A. Ovaj novi sustav dizajniran je za pružanje multimedijske usluge malim prijamnicima poput dlanovnika, a dva tipa veze; izravna satelitska veza i neizravna zemaljska veza, osiguravaju globalnu pokrivenost. Dizajniran je simulator ovog sustava kojim se analizira komunikacija sustava s razlièitim konfiguracijskim parametrima kao i komunikacija uspostavljena preko razlièitih modela komunikacijskih kanala. Na temelju simulacijskih rezultata predlaže se nova, hibridna struktura DVB-SH-A sustava temeljena na naprednim metodama modulacijskih postupaka: rotaciji dijagrama stanja. Novi hibridni DVB-SH-A model pokazuje poboljšanje komunikacije za nekoliko redova velièine (kao kriterij promatra se omjer broja krivo prenesenih bitova u odnosu na ukupan broj prenesenih bitova). Na temelju izvršenih mjerenja propagacijskog gubitka u urbanoj sredini koju odlikuje brdovito podruèje u jednom dijelu, a gdje je odašiljaè na puno veæoj visini od prijamnika, definira se model kanala koji opisuje ovakvu sredinu za frekvencije u UHF frekvencijskom podruèju. Usporedbom mjernih rezultata s vrijednostima modela kanala koje literatura spominje, pokazalo se da je potreba za novim modelom kanala opravdana. U prvoj definiciji novog modela kanala vrši se adaptacija Okumura-Hatina modela propagacijskog gubitka. U radu se, takoðer, iznosi algoritma za pronalaženje nove strukture modela komunikacijskog kanala na temelju kojeg je odreðen novi model propagacijskog gubitka. Novi model vjernije prati izmjerene vrijednosti. Na kraju, u ovom radu se na temelju simulacijskih rezultata i izvršenih mjerenja daje procjena moguænosti adaptacije DVB-SH-A sustava u promatranoj sredini. - KLJUČNE RIJEČI NA HRVATKSOM JEZIKU: Digitalni sustav satelitske radiodifuzije do malih prijenosnih ureðaja sa zemaljskom retransmisijom, Fizièki sloj sustava DVB-SH-A, Hibridna struktura fizièkog sloja DVB-SH-A sustava, Rotacija dijagrama modulacijskog postupka, Konfiguracijski parametri DVB-SH-A sustava, Kvaliteta komunikacije i prijama u razlièitim uvjetima u kanalu, Modeli komunikacijskih kanala, Propagacijski gubici, Empirijsko modeliranje propagacijskog kanala
SUMMARY: Under the Digital Video Broadcasting (DVB) umbrella different standards for digital communication are defined. The DVB organization standardized digital television with fixed reception, satellite broadcasting with fixed reception and moved on to offering digital terrestrial television to costumers with small receivers in movement. Today, they also standardized satellite broadcasting to small handheld devices i.e. receivers that are moving and receiving multimedia content transmitted from satellite, thus defining the Digital Video Broadcasting - Satellite services to Handheld (DVB-SH). The DVB-SH standard was published in February 2007 and was designed to transport mobile TV services. It also supports a wide range of mobile multimedia services, e.g. audio and data broadcast as well as file download services. Main feature of the DVB-SH system is a hybrid satellite and terrestrial infrastructure operating at frequencies below 3 GHz. The DVB-SH system coverage is obtained by combining a Satellite Component (SC) and a Complementary Ground Component (CGC). The Satellite Component covers wide areas while CGC provides cellular-type coverage as well as insurance of service continuity in areas where satellite is not able to provide expected quality of service (QoS). The system includes two different physical layer configurations: -SH-A based on the orthogonal frequency division multiplexing (OFDM) derived from the DVB-T standard. Both, the SC and the CGC use the OFDM transmission. -SH-B based on time division multiplexing (TDM) transmission mode for the SC and OFDM transmission mode for the CGC. The TDM mode is partly derived from the DVB-S2 (satellite second generation) standard. This dissertation deals with digital broadcasting from satellite to moving receivers via a terrestrial repeater where communication is based on orthogonal frequency division multiplexing. Therefore, first the physical layer of the DVB-SH-A system is described. The input stream into the physical layer of system is of type MPEG-2 or MPEG-4 although it may also be a generic input stream. After adaptation of the input stream, the message is coded by forward error correction code of type 3GPP2 (Third Generation Partnership, Project 2) and punctured with puncturing pattern defined by code rate. The DVB-SH-A system allows eight different code rates: 1/5, 2/9, 1/4, 2/7, 1/3, 2/5, 1/2 i 2/3. The DVB-SH-A system allows two modulation types: the Quadrature Phase Shift Keying and the Quadrature Amplitude Modulation with 16 constellations. The SH-A physical layer includes the OFDM that allows four different OFDM modes: 1K-OFDM, 2K-OFDM, 4-OFDM or the 8-OFDM mode, with guard interval lengths set to 1/4, 1/8, 1/16 or 1/32. All processing block in the physical layer as well as configuration parameters are described in the second chapter. The third chapter deals with different channel models already presented in literature. The main focus is on the Okumura-Hata description of propagation loss as well as ETSI and COST defined channel models for fixed and mobile reception in urban areas: channel model with Ricean or Rayleigh amplitude distribution defined with 20 taps for fixed reception, typical urban channel models defined with 6 or 12 taps for mobile reception, pedestrian indoor and pedestrian outdoor channel models for mobile reception. In the fourth chapter empirical modeling of channel models based on signal strength measurement and propagation loss calculation is given. The measurement setup is presented: the transmitter antenna placed on top of the Sljeme Hill in Zagreb (Croatia), the receiver antenna (YAGI antenna) and the signal analyzer used to measure the signal strength on different locations. Based on measured signal strength, the propagation loss was calculated since the transmitted signal strength is known for every measurement made. The first derived model is based on the Okumura-Hata definition of propagation loss: the Okumura-Hata model was adopted to better follow the measured values of propagation loss. The second model has a new structure and follows the measured values better. The fifth chapter analysis the behavior of the DVB-SH-A system in different communication scenarios. Analysis is made via use of simulation model programmed in Matlab. The verification of simulation model was made by analyzing the quasi-error-free communication established over the Gaussian channel model. Once the model showed to be good, it was used to check configuration parameter influence on communication quality in system. Also, by use of designed simulation model, the quasi-error-free communication was detected for communication established over different channel models: channel model with Ricean or Rayleigh amplitude distribution, typical urban channels defined with 6 or 12 taps and the pedestrian indoor and pedestrian outdoor channel models described with 12 taps defined for mobile reception. The sixth chapter describes possible improvement of system by introducing a hybrid physical layer of DVB-SH-A system based on rotated constellation graph. The rotation of constellation was derived from the digital video broadcasting standard for second generation of terrestrial television directly. For the same noise level in system, system with rotated diagram showed to be more robust then system using no rotation. The analysis was made by use of simulation model designed via Matlab and introduced in chapter five. Same model was used to analyze code type substitution, but the new LDPC code instead of the standard 3GPP2 showed no significant improvement in communication quality. The dissertation was concluded in chapter six where also the main contribution of the dissertation are listed: -Simulation model of satellite digital videobroadcasting with terrestrial retransmission that follows the ETSI standard for DVB-SH-A system was designed via use of Matlab. Its verification was made by simulation of quasi-error-free communication established over Gaussian channel model. -Configuration parameters of satellite digital videobroadcasting with terrestrial retransmission for urban areas of interest are chosen so that adaptation of the system in urban area of interest is possible. -Hybrid structure of physical layer of satellite digital broadcasting with terrestrial retransmission is based on rotated constellation diagram and ensures a more robust communication then standard defined physical layer with no-rotated structure. -Channel model based on empirical model for communication in urban areas for frequencies in the UHF range is based on measured propagation loss in urban area of interest. The first definition of channel model is based on adaptation of Okumura-Hata description of propagation loss. The second definition of channel model has a new structure with less parameters then the Okumura-Hata adaptation. The new model better follows measured values. - KEYWORDS: Digital video broadcasting - satellite to handheld devices with terrestrial retransmission, Physical layer of DVB-SH-A, Hybrid physical layer for DVB-SH-A system, Rotated constellation diagram, Configuration parameters of DVB-SH-A system, Communication quality and reception in different communication scenarios, Communication channel models, Propagation loss, Empirical modeling of propagation channel
Na spor. nasl. str. naslov na eng. jeziku: Communication channel model for satellite digital broadcasting with terrestrial retransmission : doctoral thesis
Bibliografija: str. 205-217. - Životopis na hrv. i eng. jeziku [uključuje i popis radova autorice]